Perancangan Tactile Picture Book untuk Siswa Tunanetra di Sekolah Dasar - Sekarlintang, Nuriana (INKLUSI, 2020)
According to the Ministry of Social Affairs census in 2012, 338.672 residents in Indonesia live with visual impairment, of which the 11.995 are children. Visually impaired children have the right to proper education facilities. Nevertheless, in Indonesia, the educational media for visually impaired children are still minimal. Children who are just learning to read the braille have difficulty reading braille texts because the system is quite complex, and the media is still conventional. The tactile picture book is a picture book that is read by touch. Children can understand images in a tactile picture book, particularly in terms of illustrations, layouts, colors, and themes adapted to Indonesian children's culture. Tactile picture books can be a medium for introducing braille letters to children in a more effective and fun way as well as media to understand the concepts and environment around them. [Menurut sensus Kementrian Sosial pada tahun 2012, sebanyak 338.672 penduduk Indonesia adalah tunanetra kategori low vision hingga totally blind, dari jumlah tersebut 11.995 diantaranya adalah anak-anak. Anak tunanetra berhak mendapatkan fasilitas pendidikan yang memadai. Namun di Indonesia, media edukasi untuk anak-anak tunanetra masih sangat terbatas. Anak-anak yang baru belajar membaca kesulitan untuk membaca teks braille karena sistemnya yang cukup kompleks dan medianya yang masih konvensional. Tactile picture book merupakan buku bergambar yang dibaca dengan perabaan. Gambar dalam tactile picture book dapat dimengerti oleh anak dengan beberapa ketentuan khusus mengenai ilustrasi, layout, warna, dan tema yang disesuaikan dengan kultur anak Indonesia. Tactile picture book dapat menjadi media pengenalan huruf braille kepada anak dengan cara yang lebih efektif dan menyenangkan sekaligus media untuk memahami konsep dan lingkungan di sekitar mereka.]